Agriscience : - Burton, L. DeVere (Thomson Delmar Learning, 2005)
Agriscience Fundamentals and Applications is the most effective book available for introducing agricultural education. It addresses the full spectrum of the agricultural industry and introduces science as the basis for higher productivity and for the safest food system in the world. Readers also gain knowledge about agricultural careers and opportunities through the Agri-Profile feature. The authors successfully convey the principles of integrating science into the agricultural curriculum, and they educate readers about accessing related material on the Internet and about National FFA programs related to agriscience and technology. Color photos and illustrations, discussions of recent technological advances and Hot Topic inserts are just some of the many tools used to help the reader comprehend the wealth of material contained in this introduction to agriscience.